Induction heat treatment of sheet-bulk metal-formed parts assisted by water-air spray cooling - Besserer, Hans-Bernward; Dalinger, Andrej; Rodman, Dmytro; Nuernberger, Florian; Hildenbrand, Philipp; Merklein, Marion; Maier, Hans Juergen (Steel Research International, 2016)
In order to produce components with massive secondary functional elements from sheet metal bulk forming operations, termed sheet-bulk metal forming, can be applied. Owing to high, three-dimensional stress and strain states present during sheet-bulk metal forming, ductile damage occurs in the form of micro-voids. Depending on the material flow properties, tensile residual stresses can also be present in the components' formed functional elements. During service, the components are subjected to cyclic loading via these functional elements, and tensile residual stresses exert an unfavorable influence on crack initiation and crack growth, and therefore on the fatigue life. Following the forming process, temperature and microstructurally related compressive residual stresses can be induced by local heat treating of the surface. These residual stresses can counteract potential crack initiation on the surface or in the subsurface regions. In the present study, the adjustability of the residual stress state is investigated using a workpiece manufactured by orbital cold-forming, which possesses an accumulation of material in its edge region. Based on residual stress measurements in the workpiece's edge region using x-ray diffractometry, it is possible to verify the compressive residual stresses adjusted by varying the cooling conditions.
LFT Import::2019-07-29 (2150)
Keywords: DP600; induction heat treatment; orbital forming; residual stress; water–air spray cooling